The demon headmaster - "Cross, Gillian" (Puffin: London, 2009)
Something is horribly wrong at Dinah's new school. The children are neat and well behaved - why is this, and why does Dinah find herself conforming? What is the secret of the headmaster's control? Dinah is determined to unravel the mystery of the sinister headmaster.
Keywords: Children's stories